Level of Knowledge and Attitudes towards the Practice of Obtaining Antibiotics among Health Students - Luthfi Nur Rohman Sudarko; Rosyidah Rosyidah; Sulistyawati Sulistyawati; Sitti Nur Djannah; Intan Wahyuni Tukiyo (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Antibiotics are one of the drugs used to treat disease problems caused by bacterial infections. Because they are used to treat bacterial infections, antibiotics should not be used without guidance from a doctor. As a result of inappropriate use, it will impact the emergence of antibiotic resistance. This research aims to determine the knowledge and attitudes of second-semester students regarding practice of obtaining antibiotics to and use of antibiotics at Faculty of Public Health of Ahmad Dahlan University (FKM UAD). This research is an analytical observational study conducted with a cross-sectional design. The population of this study was UAD FKM students in their second semester, from two different study programs. The number of respondents in this study was 127, obtained using accidental sampling. The instrument used in this research is an electronic questionnaire, which will be analyzed using chi-square analysis with a p-value 0.005. Student knowledge is in the low category (61.4%), and student attitudes are also negative (59.1%). Meanwhile, the chi-square test results show that knowledge (p-value: 0.025; PR: 2.5; 95% CI: 1.179-5.093) and attitude (p-value: 0.037; PR: 2.3; 95% CI: 1.112-4.713) have a relationship to practice of obtaining antibiotics in second-semester students at FKM UAD. Students' knowledge and attitudes are significantly related to the behaviour and practices regarding antibiotic use among FKM UAD students. It is hoped that related parties can create educational programs for students on the use of antibiotics and the importance of obtaining the right antibiotics.